Time and Philosophy : a History of Continental Thought. - McCumber, John (Taylor and Francis, 2014)
""Time and Philosophy"" presents a detailed survey of continental thought through an historical account of its key texts. The common theme taken up in each text is how philosophical thought should respond to time. Looking at the development of continental philosophy in both Europe and America, the philosophers discussed range from Hegel, Marx, Kierkegaard, Nietzsche, Husserl, Heidegger, Arendt, Adorno and Horkheimer, Sartre, de Beauvoir, Foucault, Derrida, to the most influential thinkers of today, Agamben, Badiou, Butler and Ranciere. Throughout, the concern is to elucidate the primary texts.